Personal Entrepreneurial Competences among English Students in Entrepreneurship Education - Nur ROSİTA (Ömer Gökhan Ulum, 2023)
This study aims to analyse the entrepreneurial competencies of English Language and Literature students. Through this research, a mapping of students' abilities in entrepreneurship is carried out as measured by several components that characterize entrepreneurial abilities which include 13 competencies: initiative, see and acts on opportunities, persistence, information seeking, concern for high quality of work, commitment to work contracts, efficiency orientation, systematic planning, problem solving, self-confidence, assertiveness, persuasion, use of influence strategies. A self-assessment of Personal Entrepreneurial Competence Questions (PECs) using Likert scale is administered to 103 students that randomly chosen as sampling. It is found that students' awareness toward entrepreneurial competencies is in the intermediate level that indicate to be sufficiently developed. Thus, the needs of entrepreneurship education in university include entrepreneurial teaching and entrepreneurial practice support must be considered.